Da Batman indtog elfenbenstårnet – Opgraderingen af populær- og hverdagskulturen som analyseobjekt - Fabian, Louise (Slagmark - Tidsskrift for idéhistorie, 2018)
This article discusses the different conceptualisations of popular and everyday culture and examines the diverse motivations and methods that are present in its recent upgrading as a rich source of academic analysis. Central aspects in the development of the British tradition of cultural studies are introduced to show how this tradition has developed sophisticated ways to analyse the critical and creative potentials involved in the appropriation of cultural products. Cultural studies have long held critical roots and aspirations, which have had to be reinvented within the different paradigms that explain cultural phenomena in various contexts, such as the semiotic, emotional and embodied. This critical potential and its ongoing reformulations are discussed in the article.